KESULITAN BELAJAR MATEMATIKA: ANALISIS PENGETAHUAN AWAL [DIFFICULTY IN LEARNING MATHEMATICS: PRIOR KNOWLEDGE ANALYSIS] - Panggabean, R. F. Setia Budi; Tamba, Kimura Patar (Universitas Pelita Harapan, 2020)
In line with constructivism theory, prior knowledge is important in learning. Prior knowledge is the basis for a person being able to accept any new information that has been given. The background of this paper is the recognition that a number of students have difficulty learning mathematics. The results of observations when teaching grade 12 students about the matrix show that students still have difficulty in performing addition and subtraction arithmetic operations. This fact shows that there is a problem in students' prior knowledge. This paper aims to see the importance of the position of initial knowledge in student learning difficulties. This paper is a literature review. The results obtained show that initial knowledge is a source of student learning difficulties. This can be seen from the nature of mathematics and the thinking process of students in learning mathematics. From the nature of mathematics, according to constructivism, knowledge is acquired in a progressive constructive manner. Difficulties will arise when the prior knowledge is epistemologically different from the new knowledge. From the thinking process, students use their prior knowledge to construct new knowledge or respond to new information. The implication is that learning difficulties will arise when there is a conflict between prior knowledge and new knowledge.BAHASA INDONESIA ABSTRACT: Sejalan dengan teori konstruktivisme, pengetahuan awal (prior knowledge) merupakan hal penting dalam pembelajaran. Pengetahuan awal menjadi landasan bagi seseorang untuk mampu menerima informasi baru yang telah diberikan. Hal yang melatar belakangi tulisan ini adalah banyaknya anak didik yang kesulitan belajar matematika. Hasil observasi ketika mengajar SMA kelas XII tentang matriks menunjukkan siswa masih kesulitan dalam melakukan operasi hitung penjumlahan dan pengurangan. Hal tersebut menunjukkan ada masalah dalam pengetahuan awal siswa. Tujuan penulisan adalah untuk melihat pentingnya posisi pengetahuan awal dalam kesulitan belajar siswa. Tulisan ini merupakan kajian literatur. Hasil yang diperoleh menunjukkan pengetahuan awal merupakan sumber kesulitan belajar siswa. Hal ini dilihat dari natur matematika dan proses berpikir siswa dalam belajar matematika. Dari natur matematika, menurut teori konstruktivisme, pengetahuan diperoleh secara konstruktif progresif. Implikasinya, kesulitan akan muncul ketika secara epistemology pengetahuan awal berbeda dengan pengetahuan yang akan dipelajari. Dari proses berpikir, dalam membentuk pengetahuan baru atau merespon informasi yang dihadapkan padanya, siswa menggunakan pengetahuan awalnya. Implikasinya, kesulitan belajar akan muncul ketika terjadi konflik antara pengetahuan awal dengan pengetahuan yang akan dipelajari.